SEX DETERMINATION AND AGE ESTIMATION: SKELETAL EVIDENCE FROM ST. THOMAS' CEMETERY BELLEVILLE, ONTARIO - Rogers, Tracy (My University, 1991)
The precision and accuracy of 17 pelvic an 17 cranial features commonly used to assess adult skeletal sex and three systems of adult pelvic age estimation were tested on a sample of 278 individuals from the 19th century St. Thomas' Anglican church Cemetery in Belleville, Ontario. Documentation in the form of parish burial, marriage and baptismal records exists for the entire cemetery, but only fifty-five individuals over 17 years of age are personally identified. Both the pelvic an cranial methods of morphological sex determination produce sex ratios indistinguishable from the documented ratio. on a individual basis, the precision and accuracy of the pelvic approach is superior to that of the cranial approach. The most reliable and accurate pelvic results may be obtained from an examination of the following six criteria: ventral arc, obturator foramen, true pelvis shape, sacrum shape, subpubic concavity and pubis shape. the following eight cranial criteria produced the least amount of intraobserver error and the greatest degree of accuracy: superaorbital ridges, mastoid size, malar size and shape, occipital markings, chin form, general size, zygomatic root extension and mandible shape. Three features, posterior view of the sacrum, zygomatic root extension and occipital muscle markings, exhibit increases accuracy with age. There is no age-related affect on accuracy when the complete trait lists are employed. Pelvic assessments appear to be biased in favour of males while cranial assessments seem biased in favour of females. Of the Phenice (1969) criteria, the ventral arc is the single most useful trait exhibiting both high precision (0% intraobserver error) and high accuracy (86.9%). The subpubic concavity ranked second and the ischiopubic ramus last. None of the age techniques examined in this investigation are precise and accurate enough to be employed exclusive of other systems. When both precision and accuracy are taken into account, the auricular surface technique of estimating skeletal age-at-death produces the best results for individual cases. One major problem with this method is its tendency to overage individuals less than 40 years and underage indviduals greater than 40 years. The accuracies of the Suchey methods are acceptable mainly ecause of the wide age ranges covered by each phase. The estimates provided by these methods are too broad to be useful in individual cases. When used to produce an age profile the Suchey systems (with the Jackes (1985) distribution method) are better than the auricular surface method. The pattern is slightly distorted by problems associated with phases III (2), IV (1) and IV.
Keywords: Anthropology; Anthropology